A Clinical Study Of Different Causes & Quality Of Life In Unilateral Sensorineural Hearing Loss - Faiyaz, Falaq; Kumar Verma, Pankaj; Singh, Ranveer (Journal of Neonatal Surgery, 2025)
Background: Unilateral sensorineural hearing loss (USNHL) affects one ear and can impact communication and quality of life. It has varied causes, often remaining idiopathic despite evaluation. This study explores the underlying causes and their effect on quality of life to guide timely diagnosis and management. Method: This descriptive prospective study was conducted at the ENT department of IIMSR from May 2023 to December 2024. Patients aged 7 years and above with unilateral sensorineural hearing loss were evaluated through audiological tests, vestibular assessments, BERA, and MRI when indicated. Blood tests assessed metabolic and inflammatory markers. Quality of life was measured using HEAR-QL for children and AQoL-8D for adults. Results: Most participants were middle-aged, and tinnitus emerged as the most common associated symptom. Idiopathic causes were the predominant etiology, followed by sudden sensorineural hearing loss (SSNHL) and Meniere’s disease. A satisfactory quality of life (QOL) was reported by 58.5% of patients. No statistically significant association was found between QOL and factors such as age, gender, hearing threshold (PTA), comorbidities, or biochemical markers. However, a shorter duration of hearing loss was significantly linked to bad QOL (p = 0.001). These findings highlight the importance of early diagnosis, comprehensive evaluation, and timely management to enhance patient outcomes. Conclusion: Idiopathic causes were the most common in USNHL, followed by SSNHL, Meniere’s disease, and congenital factors. Tinnitus was the most frequent symptom, often with vertigo. Many cases remained unexplained despite thorough evaluation. Quality of life was more affected in recent-onset cases, though not linked to age or severity. Early diagnosis, rehabilitation, and public awareness are key to improving outcomes.